NUMERICAL SIMULATIONOF FLEXIBLE WINGOF HALE UAV USING TWO-WAY FLUID STRUCTURE INTERACTION METHOD - Junaidin, Buyung (Sekolah Tinggi Teknologi Adisutjipto, 2017)
This paper describes numerical simulation o f flexible High Altitude Long Endurance Unmanned Aerial Vehicle (HALE UAV)wingusing two-way fluid structure interaction (FSI) method. The HALE wing is designed with high aspect ratio. This configuration intended to reduce the vehicle induced drag and reduces the lift-loss at wingtip which caused by wingtip vortex. But the structure of the wing itself becomes more elastic that be able to give large deformation when the aerodynamic loads applied. This deformation changes the aerodynamic loads distribution on the wing that gives a new deformation to the wing structure and vice versa. This interaction in a couple process called as fluid structure interaction (FSI). ANSYS 15.0 software was used to simulate fluid structure interaction on the wing. The unsteadiness and viscous flows at low speed are evaluated using the solution o f timedependent Reynolds Averaged Navier-Stokes (RANS) with SST k-rn turbulent model. In addition, multiblock structured grids are generated to provide more accurate viscous result and to anticipate negative volume o f the mesh which may occur due to the deformation o f the wing during simulation. Five different o f simulations are performed with variation o f material characteristics including Youngâs modulus and Poissonâs ratio.The results are global aerodynamic characteristics at various material characteristics.